The Supreme Court and executive law-making: the afterlife of failed ordinances in Krishna Kumar Singh II. Issue 3 (2nd September 2017) - Mukherjee, Gaurav
ABSTRACT: In Krishna Kumar Singh v. State of Bihar, the Supreme Court of India (SCI) considered the legality and repercussions of a series of re-promulgated ordinances by the Governor of Bihar. I critically analyse the judgement on four counts: conditions for valid promulgation of an ordinance, the survival of actions under failed ordinances, justiciability of executive satisfaction over necessity of promulgating an ordinance, and legality of re-promulgating ordinances. I suggest that while the SCI authoritatively establishes the conditions for valid promulgation of an ordinance, its holding on the legality of re-promulgation and the survival of actions under failed ordinances are not adequately narrow to prevent the possibility of abuse by the executive. Further, the Court's unwillingness to apply a more searching standard of review for executive satisfaction when promulgating ordinances also does little to advance its existing jurisprudence and may prove to be unhelpful in deciding future cases where the existence of emergent conditions is in question.